2019
DOI: 10.33545/gynae.2019.v3.i2a.09
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nonstress test in improving the perinatal outcome in pregnancies complicated by preeclampsia

Abstract: Introduction: Antepartum fetal surveillance is the assessment of fetal well being in utero before the onset of labour. It helps in early detection of fetuses at risk, so that timely management can prevent further deterioration, thereby reducing perinatal morbidity / mortality. Around 10-30% of the mothers seen in antenatal period can be classified as high risk but they account for 70-80% of perinatal mortality / morbidity. Aim And Objectives: The role of NST in management of pregnancies complicated by preeclam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
1
0
0
Order By: Relevance
“…(p <0.001). Similar results were seen in a study conducted by Jamatia A et al 33 Bagum et al 81 observed that reactive NST group showed favourable fetal outcome and non-reactive NST showed significant increase in overall abnormal outcome, low 1 & 5 minute Apgar score, more NICU admissions and more perinatal mortality rates. 34 They concluded that NST is a valuable tool for the assessment of fetal wellbeing in high risk pregnancies.…”
Section: Methodssupporting
confidence: 84%
“…(p <0.001). Similar results were seen in a study conducted by Jamatia A et al 33 Bagum et al 81 observed that reactive NST group showed favourable fetal outcome and non-reactive NST showed significant increase in overall abnormal outcome, low 1 & 5 minute Apgar score, more NICU admissions and more perinatal mortality rates. 34 They concluded that NST is a valuable tool for the assessment of fetal wellbeing in high risk pregnancies.…”
Section: Methodssupporting
confidence: 84%
“…It facilitates early detection of fetuses at risk, so timely management can prevent further damage and thus reduce perinatal morbidity/mortality. 4 NST is considered as a good predictor of fetal health and is recommended after 32 weeks of pregnancy. Prenatal Non stress test is also a component of Biophysical profile.…”
mentioning
confidence: 99%